2009
DOI: 10.1148/rg.295095109
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Lesions of the Central Nervous System: Radiologic-Pathologic Correlation

Abstract: Pigmented lesions of the central nervous system (CNS) are a diverse group of entities that run the gamut from benign to malignant. These lesions may be well circumscribed or diffuse, and their imaging appearances are influenced by the degree of melanin content as well as the presence or absence of hemorrhage. Pigmented lesions include primary melanocytic lesions of the CNS and metastatic melanoma, as well as other CNS neoplasms that may undergo melanization, including schwannoma, medulloblastoma, and some glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
161
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(176 citation statements)
references
References 78 publications
4
161
1
8
Order By: Relevance
“…5,9 The clinical signs and symptoms depend on its location and may present as myelopathy and seizures. 10,12 The symptoms of our patients were nonspecific, mainly caused by mass compression.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…5,9 The clinical signs and symptoms depend on its location and may present as myelopathy and seizures. 10,12 The symptoms of our patients were nonspecific, mainly caused by mass compression.…”
Section: Discussionmentioning
confidence: 72%
“…6,7,10,11 The annual incidence of MM is estimated to be 1 case per 10 million people, and women are vulnerable. 10 Our hospital has an extremely large collection area for patients from Guangdong province and 4 neighboring provinces. The orthopedics center in our hospital is very famous and is also a referral center for spinal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher melanin concentration was associated with higher signal intensities on T1W images and lower signal intensities on T2W images. 15 In CNS melanoma, this typical sign was observed in less than half of the patients; 16 however, in our review of PSM of extramedullary origin, these typical changes were observed in 95% (20/21) of patients. Therefore, when an intraspinal extramedullary tumor shows hyperintense T1W and hypointense T2W signaling, melanoma should be suspected.…”
Section: Discussionmentioning
confidence: 70%
“…Spinal schwannoma or meningioma lacks the characteristic signals (hyperintensity on T1W and hypointensity on T2W) on MRI examination, even in pigmented schwannoma or meningioma. 15 Spinal extramedullary hematoma usually presents with intense, 'knife-like' pain at the location of the hemorrhage ('coup de poignard') and subsequently progressive paralysis below the affected spinal level. These clinical features are different from those of primary melanoma.…”
Section: Discussionmentioning
confidence: 99%